2021
DOI: 10.3390/nu13051405
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Early Time-Restricted Feeding on Metabolic Diseases: Importance of Aligning Food Habits with the Circadian Clock

Abstract: The importance of metabolic health is a major societal concern due to the increasing prevalence of metabolic diseases such as obesity, diabetes, and various cardiovascular diseases. The circadian clock is clearly implicated in the development of these metabolic diseases. Indeed, it regulates physiological processes by hormone modulation, thus helping the body to perform them at the ideal time of day. Since the industrial revolution, the actions and rhythms of everyday life have been modified and are characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 139 publications
3
62
1
6
Order By: Relevance
“…Although there have been many studies discussing the timing of food intake, the irregularity of mealtimes was not the main focus of these studies [ 33 ]. For instance, breakfast skipping and nighttime snacking have been found to be associated with evening chronotype with greater social jet lag, which has also been associated with obesity or lifestyle-related diseases [ 11 , 12 , 13 , 20 ]. Breakfast skipping has also been confirmed to be associated with a higher incidence of obesity and hyperlipidemia [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been many studies discussing the timing of food intake, the irregularity of mealtimes was not the main focus of these studies [ 33 ]. For instance, breakfast skipping and nighttime snacking have been found to be associated with evening chronotype with greater social jet lag, which has also been associated with obesity or lifestyle-related diseases [ 11 , 12 , 13 , 20 ]. Breakfast skipping has also been confirmed to be associated with a higher incidence of obesity and hyperlipidemia [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to specific food groups, eating behavior is also an important factor in this regard. Breakfast skipping has been associated with higher levels of stress, depression, and fatigue [ 11 , 12 ]. Patients with night eating syndrome (NES) show nocturnal emotional eating with a higher depressed mood in the evening and lower sleep quality [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence that the timing of food intake influences the development of overweight, obesity, and metabolic disorders [ 35 , 36 ]. Hence, based on the evolutionary circadian rhythm of metabolism, early TRE is investigated on its presumed better effects on metabolic markers [ 14 ], and evidence is accumulating for the superiority of an earlier versus a later time window of food intake in TRE [ 15 ]. Currently, there are mainly smaller studies, often of a pilot character, that address this hypothesis, and against this background, most of the results presented below should therefore be viewed critically.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are mainly smaller studies, often of a pilot character, that address this hypothesis, and against this background, most of the results presented below should therefore be viewed critically. Several studies of early TRE with stopping food intake before 19:00 h resulted in better weight loss, while late eating showed reduced beneficial effects [ 14 ]. A crossover study with 11 participants showed that eating three meals between 08:00 and 14:00 resulted in improved glucose response and detection of markers of circadian rhythmicity and autophagy as compared to a control schedule from 08:00 to 20:00 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation